2007
DOI: 10.1038/nature06261
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule activators of SIRT1 as therapeutics for the treatment of type 2 diabetes

Abstract: Calorie restriction extends lifespan and produces a metabolic profile desirable for treating diseases of ageing such as type 2 diabetes. SIRT1, an NAD+-dependent deacetylase, is a principal modulator of pathways downstream of calorie restriction that produce beneficial effects on glucose homeostasis and insulin sensitivity. Resveratrol, a polyphenolic SIRT1 activator, mimics the anti-ageing effects of calorie restriction in lower organisms and in mice fed a high-fat diet ameliorates insulin resistance, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,415
12
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,542 publications
(1,478 citation statements)
references
References 27 publications
(12 reference statements)
46
1,415
12
5
Order By: Relevance
“…Chemopreventative strategies may also counter age-associated diseases other than cancer. Remarkably, addition of a SirT1 activator, resveratrol, to the diet of mice fed a high fat diet prolongs the healthy lifespan of those mice [114,115], apparently mimicking the well-established contribution of dietary caloric restriction to longevity [116]. Although there are questions as to whether resveratrol extends lifespan through SirT1 and whether SirT1 acts through chromatin [117,118], these studies demonstrate the potential of chemopreventative strategies to combat aging.…”
Section: Summary Outstanding Questions and Therapeutic Implicationsmentioning
confidence: 71%
“…Chemopreventative strategies may also counter age-associated diseases other than cancer. Remarkably, addition of a SirT1 activator, resveratrol, to the diet of mice fed a high fat diet prolongs the healthy lifespan of those mice [114,115], apparently mimicking the well-established contribution of dietary caloric restriction to longevity [116]. Although there are questions as to whether resveratrol extends lifespan through SirT1 and whether SirT1 acts through chromatin [117,118], these studies demonstrate the potential of chemopreventative strategies to combat aging.…”
Section: Summary Outstanding Questions and Therapeutic Implicationsmentioning
confidence: 71%
“…These individuals are more susceptible to type 2 diabetes, cardiovascular disease, stroke, and a host of other age-related diseases. Studies in mice and humans have shown that resveratrol can lower glucose levels and may be an effective intervention for the treatment of type 2 diabetes, a disease that is prevalent in both aging and obesity Milne et al 2007;Szkudelska and Szkudelski 2010). Resveratrol has also been shown to reduce oxidative damage in human cells and animal models (Szkudelska and Szkudelski 2010;Baur 2010;Frankel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies point to Sirt1 as a chief regulator of NO synthesis in endothelium (Milne et al 2007;Pillarisetti 2008;Potente et al 2007) employing an Akt-mediated pathway of eNOS phosphorylation (Lovren et al 2009) or promoting eNOS catalytic activity through deacetylation of lysines 496 and 506 (Mattagajasingh et al 2007). As NO itself appears to reciprocally activate Sirt1 expression and activity (Ota et al 2007), then Sirt1-eNOS axis emerges as a decisive regulatory mechanism in CC endothelium.…”
Section: Discussionmentioning
confidence: 99%